Between Empires, Among Believers: A Microhistorical and Borderland Analysis of Benedikt Kuripešić’s 1530 Travel Diary - Srđan Jovanović (Journal of Balkan Studies)
This article offers a microhistorical and borderland-centered analysis of Benedikt Kuripešić’s 1530-1531 travel diary, composed during a Habsburg diplomatic mission to Ottoman Constantinople. Often cited yet rarely studied in depth, Kuripešić’s text is reinterpreted here as more than a record of geographic movement; it is a rich epistemic artifact that captures early modern inter-imperial friction in the Balkan borderlands. Drawing on the methodologies of Carlo Ginzburg and Anssi Paasi, the article argues that Kuripešić’s diary reveals how borders were experienced not only through political boundaries but through affective registers: faith, fear, memory, and resistance.